Передумови розвитку антикризового управління в економічній системі України - Кібік, Ольга Миколаївна; Кибик, Ольга Николевна; Kibik, Ol'ga; Котлубай, В'ячеслав Олексійович; Котлубай, Вячеслав Алексеевич; Kotlubaj, Vjacheslav (My University, 2013)
The article is devoted the questions of the crisis management on the different levels of the economic system, particular in the field of functioning the maritime economy. The basic problems of crisis management are certain. The criterion of the use of direct state financial support of marine economy is offered for realization of effective state crisis management.
Кібік О. М., Котлубай В. О. Передумови розвитку антикризового управління в економічній системі України / О. М. Кібік, В. О. Котлубай // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 213-219.
Keywords: криза; антикризове управління; фінансова підтримка; морегосподарський комплекс; кризис; антикризисное управление; финансовая поддержка; морехозяйственный комплекс; crisis; crisis management; financial assistance; maritime complex